The Impact of Religiosity and Social Support on Psychological Well-Being among Tahfidz Students - Sukmawati, Shinta; Husna, Sabiqotul (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
High school students who memorize Al-Qur'an face challenges maintaining their psychological well-being while memorizing Al-Qur'an and attending school activities. This study aims to determine the relationship between religiosity and social support with psychological well-being in high school students who memorize the Qur'an. The research subjects were 103 students (mean age 16.41) who were in the process of memorizing 30 chapters of the Qur’an at SMA IT Abu Bakar and SMA IT Baitussalam Yogyakarta. The sampling technique used was convenience sampling. Data collection was carried out using three scales: psychological well-being scale (α=0.904), religiosity scale (α=0.892), and social support scale (α=0.092), all of which were modified. The multiple regression data analysis revealed a significant relationship between religiosity and social support with the psychological well-being of high school students who memorize the Qur'an. The simultaneous effective contribution of two independent variables to psychological well-being is 52.6%. The partial contribution of religiosity is 26.9%, and the partial contribution of social support is 25.7%. These results can be a baseline for schools to develop support for memorizing the Qur'an in terms of facilities, training, and mentoring to increase students' religiosity and psychological well-being.